Low-density lipoprotein particles in atherosclerosis - Qiao, Ya-Nan; Zou, Yan-Li; Guo, Shou-Dong (Frontiers in Physiology, 2022)
Atherosclerosis is the prominent root of cardiovascular disease (CVD), contributing to the most considerable number of morbidity and mortality worldwide. Low-density lipoprotein (LDL) plays a chief role in the development and progression of atherosclerotic CVD (ASCVD). LDL cholesterol (LDL-C) remains the traditional marker of LDL. However, large numbers of patients who have achieved the recommended LDL-C goals still at the CVD risk. In multiple prospective studies, LDL particles (LDL-Ps) have been proven to be more predictive for CVD risk than LDL-C. LDL-Ps vary in size, density and chemical composition. Numerous clinical studies have proved that the atherogenic mechanisms of LDL-Ps are determined not only by number and size but also by modifications. It is well documented that small dense LDL (sdLDL) has a greater atherogenic potential than other LDL subfractions. Besides, oxidized LDL (ox-LDL) has also been a major risk factor in atherosclerosis. Of the marketed lipid lowering drugs, statins induce the greatest reductions in LDL-C and LDL-P. Recently, proprotein convertase subtilsin/kexin type 9 inhibitors (PCSK9i) have gradually been proved to be effective in lowering LDL-C and LDL-Ps as well as CVD events. In this article, we will make a short review of LDL metabolism, discuss the discordance between LDL-C and LDL-P, mainly focus on LDL-Ps with specific properties, sdLDL and ox-LDL to explore the atherogenic metabolism of LDL, summarize measurements for LDL profile, and outline the current findings and advances of LDL-lowering therapies using statins and PCSK9i.